2015
DOI: 10.1039/c5dt02076j
|View full text |Cite
|
Sign up to set email alerts
|

A self-assembled octanuclear complex bearing the uncommon close-packed {Fe4Mn44-O)4(μ-O)4} molecular core

Abstract: A one-pot open-air reaction of manganese powder with iron(ii) chloride in DMF solution of the Schiff base (H2L) formed in situ from salicylaldehyde and hydroxylamine hydrochloride yields the heterometallic complex [Fe4(μ4-O)4Mn4(L)8(DMF)4]·2DMF (). Single crystal X-ray analysis shows that its molecular structure is based on the octanuclear core {Fe4Mn4(μ4-O)4(μ-O)4} with a quite rare molecular structure type {M8(μ4-X)4(μ-X)4}, where the central cube-like iron motif is modified with four terminal manganese frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Manganese complexes 1 – 8 were obtained via the “direct synthesis” (DS) approach, which is based on using regular metal powders instead of their salts as a source of metal. This method has been widely investigated by our group, , and it has been shown that in some cases there are advantages in exploiting DS conditions as compared to the traditional “wet” chemistry. For example, a better morphology of the crystal products and absence of contaminating anions were noticed.…”
Section: Resultsmentioning
confidence: 99%
“…Manganese complexes 1 – 8 were obtained via the “direct synthesis” (DS) approach, which is based on using regular metal powders instead of their salts as a source of metal. This method has been widely investigated by our group, , and it has been shown that in some cases there are advantages in exploiting DS conditions as compared to the traditional “wet” chemistry. For example, a better morphology of the crystal products and absence of contaminating anions were noticed.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, 1 provides the first example of the homometallic oxide cluster possessing this type of structure . It is also noteworthy that octanuclear complexes having a central {M 4 (μ 4 -X) 4 } cube (M = a metal atom; X = a bridging atom) modified with four additional metal-containing units analogous to 1 are limited in number as mentioned by Kokozay and Pombeiro et al…”
Section: Resultsmentioning
confidence: 99%
“…One area lacking is the use of two different transition-metal ions in an archetypal MC. While several examples of heterobimetallic 3d 'collapsed' metallacrowns, species without a central MC cavity and thus no central metal ion (Psomas et al, 2001;Gole et al, 2010), and inverse metallacrowns, species that bind a non-metal atom in the central MC cavity to the ring metal ions (Szyrwiel et al, 2013;Shiga et al, 2014;Zhang et al, 2014;Nesterova et al, 2015), have been reported, only two heterobimetallic 3d archetypal 12-MC-4 compounds have been described to date. In 2014, Happ and Rentschler reported a Cu II (DMF) 2 Cl 2 [12-MC Fe(III)N(shi) -4](DMF) 4 Á2DMF compound ISSN 2056-9890 that contains Fe III ions in the ring positions and a Cu II ion captured in the central MC cavity (Happ & Rentschler, 2014).…”
Section: Chemical Contextmentioning
confidence: 99%